Metabolic, ventilatory, and hygric physiology of a South American marsupial, the long-furred woolly mouse opossum - Cooper, Christine; Withers, P.; Cruz-Neto, A. (2010)
The physiology of the long-furred woolly mouse opossum (Micoureus paraguayanus) conformed to that of other marsupials. Body temperature at thermoneutrality (all values reported as mean ± SE) was 33.3°C ± 0.3°C and basal metabolic rate was 0.760 ± 0.074 ml 02 g−1 h−1. Opossums were thermolabile at low ambient temperature (Ta) but still maintained a considerable differential between body temperature and Ta, with an increase in metabolic heat production as Ta decreased. This was accommodated by an increase in minute volume, mediated by an increase in both respiratory frequency and tidal volume at low Ta. Basal respiratory frequency was 34.2 ± 3.8 breaths/min and tidal volume was 1.62 ±0.28 ml; minute volume was 53 ± 7 ml/min. Oxygen extraction remained constant at 13.6% ± 1.1%. Wet thermal conductance was high (0.338 ± 0.091 ml 02 g−1 h−1 °C−1; 185% of predicted) but conformed statistically to that of other marsupials. A positive relationship existed between ambient temperature and evaporative water loss; standard evaporative water loss was 2.03 ± 0.21 mg H2O g−1 h−1. The point of relative water economy was 11°C, the lowest yet measured for a marsupial. We found no evidence that this South American marsupial had an elevated metabolic physiology, as might be expected from its neotropical distribution and sympatry with placental mammals. Clearly, marsupials can survive alongside placental mammals without any specific physiological adaptation, although this ability may be restricted to species with generalized low-energy ecological niches.